PENYULUHAN MENGENAI PEMBUATAN SUMUR RESAPAN SEBAGAI KONSERVASI SUMBERDAYA AIR, DI KECAMATAN SUKMAJAYA KELURAHAN CISALAK, DEPOK, JAWA BARAT - Melati Ferianita Fachrul; Diana Irvindiaty Hendrawan; Astri Rinanti; Lailatus Siami; Widyo Astono; Bambang Iswanto (JUARA: Jurnal Wahana Abdimas Sejahtera, 2020)
The PKM activity aims to provide counseling and training on flood prevention efforts by managing residential areas by making infiltration wells in residential areas of local residents. To achieve the goals and objectives of this PKM activity carried out by Counseling methods. The results of the implementation of PKM activities are expected to be able to add insight and knowledge to the residents of the Kelurahan of Cisalak regarding environmental conditions related to water resources conservation. Therefore, both directly and indirectly the PKM activities are expected to change the behavior of local people who are more environmentally friendly. The results of this activity concluded that this PKM activity helped add insight and information to the residents of Cisalak Kelurahan, Sukmajaya Subdistrict, Depok, relating to the issue of water conservation by making infiltration wells, by making infiltration wells, so that it is necessary to make infiltration wells in accordance with the correct manufacturing techniques as a form tangible that can be applied to the environment in which they live and the wider environment